Oxidized LDL and LOX-1 in Experimental Sepsis - Nadia Al-Banna; Christian Lehmann (Hindawi Limited, 2013)
Oxidized low-density lipoproteins (oxLDL) and the lectin-like oxLDL receptor-1 (LOX-1) are upregulated in inflammation. Because of the importance of inflammation and capillary leakage in the impairment of the microcirculation, which in turn contributes to the development of sepsis and multiorgan failure, the role of oxidized LDL and LOX-1 as players of intestinal inflammation is of great interest. In fact, the blockade of LOX-1 during experimental endotoxemia was effective in reducing leukocyte activation. There are several mechanisms by which oxLDL can participate in local and systemic inflammation, including cell proliferation, apoptosis, capillary perfusion, leukocyte-endothelial cell interactions, and endothelial activation. This review highlights the evidence relating oxLDL and LOX-1 to proinflammatory disease mechanisms. We also indicate situations when oxLDL, because of exposure time, dose, or degree of oxidization, is involved in disease resolution. Modulation of LOX-1 response could be utilized for the treatment of local and systemic inflammation, but the successful use of this target requires further understanding of its broad effects.